2013
DOI: 10.1371/journal.pone.0070548
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Coronaviral Poly(A) Tail Length during Infection

Abstract: The positive-strand coronavirus genome of ~30 kilobase in length and subgenomic (sg) mRNAs of shorter lengths, are 5’ and 3’-co-terminal by virtue of a common 5’-capped leader and a common 3’-polyadenylated untranslated region. Here, by ligating head-to-tail viral RNAs from bovine coronavirus-infected cells and sequencing across the ligated junctions, it was learned that at the time of peak viral RNA synthesis [6 hours postinfection (hpi)] the 3’ poly(A) tail on genomic and sgmRNAs is ~65 nucleotides (nt) in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
86
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(93 citation statements)
references
References 39 publications
7
86
0
Order By: Relevance
“…In coronaviruses, however, the mechanisms by which the two processes are regulated remain unclear. Based on the results from the current study and others, (i) the poly(A) tail can be bound by PABP and function in translation (46), (ii) the poly(A) tail is a start site for negative-strand RNA synthesis (47), (iii) the poly(A) tail can also be bound by the N protein with high affinity (Fig. 1), (iv) the N protein can interact with viral replicase proteins (8)(9)(10)(11)(12)(13)(14) and nsp9 ( Fig.…”
Section: Discussionmentioning
confidence: 64%
“…In coronaviruses, however, the mechanisms by which the two processes are regulated remain unclear. Based on the results from the current study and others, (i) the poly(A) tail can be bound by PABP and function in translation (46), (ii) the poly(A) tail is a start site for negative-strand RNA synthesis (47), (iii) the poly(A) tail can also be bound by the N protein with high affinity (Fig. 1), (iv) the N protein can interact with viral replicase proteins (8)(9)(10)(11)(12)(13)(14) and nsp9 ( Fig.…”
Section: Discussionmentioning
confidence: 64%
“…This requirement corresponds well to the minimal binding site of the poly(A)-binding protein (PABP) on DI RNAs poly(A) sequences (Spagnolo and Hogue, 2000). Recent studies further suggest that 3 0 poly(A) tail lengths may vary between 30 and 65 nt in the course of viral replication in vitro (Wu et al, 2013) as was shown for both beta-and gammacoronavirus infections and in a range of cell types, both in vitro and in vivo (Shien et al, 2014). The biological significance of these observations is currently unclear.…”
Section: 0 -Terminal Poly(a) Tailmentioning
confidence: 56%
“…The resulting set of 3 0 antileadercontaining sg minus-strand RNAs is subsequently used as templates for the production of the characteristic nested set of 5 0 leader-containing mRNAs in coronavirus-infected cells (Lai et al, 1983;Sawicki and Sawicki, 1995;Sawicki et al, 2001;Sethna et al, 1989;Spaan et al, 1983). Sg minus-strand RNAs contain a U-stretch at their 5 0 end, providing a possible template for 3 0 polyadenylation of sg mRNAs Wu et al, 2013).…”
Section: Coronavirus Genome Replication and Transcriptionmentioning
confidence: 99%
“…This requirement corresponds well to the minimal binding site of the poly(A)-binding protein (PABP) on DI RNAs poly(A) sequences (Spagnolo and Hogue, 2000). Recent studies further suggest that, in the course of BCoV infection, 3 poly(A) tail lengths vary between 30 and 65 nts (Wu et al, 2013). This poly(A) tail length variation was confirmed to occur in beta-and gammacoronavirus infections and in a range of cell types, both in vitro and in vivo (Shien et al, 2014).…”
Section: ' 5'mentioning
confidence: 63%
“…The set of 3 antileader-containing sg minus-strand RNAs is subsequently used as templates for the production of the characteristic nested set of 5 capped, 5 leader-containing and 3 -polyadenylated sg mRNAs in coronavirus-infected cells (Lai et al, 1983;Sawicki et al, 2001;Sawicki and Sawicki, 1995;Sethna et al, 1989;Spaan et al, 1983). Sg minus-strand RNAs contain a U-stretch at their 5 end, thus providing a template for 3 polyadenylation of sg mRNAs Wu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%